Payment choice in international trade: theory and evidence from cross-country firm-level data - Hoefele, Andreas; Schmidt-Eisenlohr, Tim; Yu, Zhihong (Wiley, 2015)
When trading across borders, firms choose between different payment contracts. Theoretically, this should allow firms to trade-off differences in financing costs and enforcement across countries. This paper provides evidence for this hypothesis employing firm-level data from a large number of developing countries. As predicted, international transactions are more likely paid after delivery when financing costs in the source country are high and when contract enforcement is low. We extend the theory and also show empirically that the more complex an industry is, the more important is contract enforcement and the less important are financing costs for the contract choice.